Canker and Dieback of Acacia nilotica Seedlings in Nursery - Uniyal, Kamla; Harsh, N. S. K.; Uniyal, D. P.; Verma, Sanjay (Indian Forester, 2004)
An outbreak of a new canker and dieback disease was recorded in Acacia nilotica seedlings. The causal organism was identified as Fusarium lateritium f. sp. acaciae f. sp. nov. and perithecial stage belongs to Gibberella. The disease was controlled by three sprays of mixture of Carbendazim and Copper oxychloride and mixture of Carbendazim and Dithane M-45.